Trail of the mountain man - Johnstone, William W. (New York Kensington Pub. Corp., 2000)
The second book in Johnson's legendary series finds Smoke Jensen in No-Name, Colorado, where every two-bit gunslick has come to get in on the gold strike. Outnumbered 100 to one, Smoke recruits his own army of aging but lethal frontier legends to put a stop to the trouble
"Pinnacle Books."
96145
Keywords: Jensen, Smoke (Fictitious character); Mountain life; Rocky Mountains; Western stories